Cointegration of Stock Market and Exchange Rate in Indonesia - Pantas, Pribawa E; Ryandono, Muhamad Nafik Hadi; Munir, Misbahul; Wahyudi, Rofiul (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2019)
This study aims to determine the long-term relationship between stock market and exchange rate in Indonesia. The research method used is Johansen cointegration test. The results of this study found no cointegration between the variables tested. Thus the exchange rate, JII, and IHSG have no relationship in the long term. The fluctuation of the rupiah exchange rate in recent years did not generally affect the performance of stock indices especially after the global financial crisis of 2008. This shows the capital market in Indonesia has a good performance so that it is not so sensitive to the sentiment of the decline in the rupiah against the US dollar. This finding is in line with the findings of Syahrer (2010) which states the exchange rate has no effect on the stock market.